The Effects of Different Irrigation Levels and Nitrogen Rates on Peanut Yield and Quality in Southeastern Anatolia Region of Turkey - Boydak, Erkan; Şimşek, Mehmet; Demirkıran, Ali Rıza (KAHRAMANMARAS SUTCU IMAM UNIV REKTORLUGU, 2021)
The aim of research about irrigation and nutrition of peanut is to determine most suitable irrigation level and nitrogen fertilizer dose for peanut in the Harran conditions (Sanliurfa, Turkey).In this study, different amounts of the nitrogen (N-1:0, N-2:40, N-3:80, and N-4:120 kg N ha(-1)) were applied as ammonium nitrate in two times as planting and flowering times to peanut plants. The irrigation levels were determined as 100, 75, 50, and 25% of the irrigation required and labeled as I-1 (first irrigation), I-2 (second irrigation), I-3 (third irrigation), and I-4 (fourth irrigation), respectively. In this study, positive and significant effect were found that the need protein and the increasing of peanut yield with its components were increased with 120 kg ha(-1) nitrogen fertilization (N-4) and no-deficit water (100%:I-1) while the variable 100 fruit weight were increased with 80 kg ha(-1) nitrogen fertilization (N-3) and no-deficit water (100%:I-1) application on plant. The plant height and 100 seed weight except 2nd year were also increased with 80 kg ha(-1) nitrogen (N-3) and no-deficit water (100%:I-1).
Keywords: Nitrogen fertilizer; Irrigation; Peanut; Arachis hypogaea L.; Harran